Cases of otology malpractice appeals to the Council of Forensic Medicine: An evaluation of the past two decades - Evcimik, Muhammed Fatih; Aslıyüksek, Hızır; Orhan, Zeynel Abidin; Cırık, Ahmet Adnan; Bayazıt, Yıldırım Ahmet; Orhan, Kadir Serkan (Royal Belgian Society for Ear, 2017)
Cases of otology malpractice appeals to the Council of Forensic Medicine: an evaluation of the past two decades. Introduction: The present study aims to demonstrate the profile of clinical malpractice by evaluating otologyrelated cases, which have been subject to legal action, to determine avoidable errors and identify actions necessary for safe clinical practices.Method: Files of otology-related malpractice appeals to the Council of Forensic Medicine between 1995 and 2015 were evaluated retrospectively. Patients' demographics, complications subject to legal action, performed operations and medical practices, medical centres where the practices took place, and whether physician error was involved, as detailed in these files, were studied.Results: A total of 44 otology-related cases was included in the study. Thirty-two (72.7%) of these were due to surgical errors and 12 (27.3%) were due to outpatient clinic services. When examined by year, there was a significant increase during the latter years. Hearing loss was the main reason for complaint with 19 cases (43.2%), followed by facial paralysis with 17 cases (38.6%), and less commonly by late diagnosis, disfigurement and tinnitus. Second-line healthcare institutions were the source of 75% of the cases. Lawsuit rationales involved under-treatment or wrong treatment, rather than wrong or late diagnosis. Three fated cases were subject to lawsuits. According to the evaluation of the files from the Council of Forensic Medicine, there were faults in eight files, while 36 files involved no faults.Conclusion: The most common causes for law suits were hearing loss and facial paralysis. Most of the lawsuits were associated with surgical cases. The retrospective analysis of otology-related malpractice files is an important step in minimizing physician errors.
Keywords: Otology; Malpractice; Medical Error; Forensic Medicine